Humidity Sensors Based on 3D Porous Polyelectrolytes via Breath Figure Method. (14th November 2019) - Dai, Jianxun; Zhao, Hongran; Lin, Xiuzhu; Liu, Sen; Fei, Teng; Zhang, Tong
Abstract: A 3D porous P4VP film prepared via breath figure (BF) is used for quaternization to synthesize humidity‐sensitive polyelectrolytes. By combining the BF method, gaseous crosslinking, and screen‐printed electrodes, humidity sensors with good stability and a fast response to humidity change are obtained, thus making them possible for application in human breath monitoring. The water molecule adsorption of the porous polymer under different RHs is investigated using a quartz crystal microbalance. Cole–Cole plots and ionic conductivity change show that these devices function as humidity sensors under different humidity atmospheres. Abstract : 3D porous polyelectrolytes are fabricated via the breath figure method and gaseous crosslinking. The adsorption capacity of this porous structure is measured by using QCM technology. Porous‐polyelectrolyte‐based electronic devices have great potential in humidity detection and respiration monitoring.